Implementasi Serangan Black Hole pada Mobile Ad-Hoc Network dengan Pergerakan Dinamis Terstruktur menggunakan Protokol Dynamic Source Routing - Tasrahmiati Istiqomah; Reza Andria Siregar; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
MANET is one of the wireless technologies that consists of several mobile nodes that are structuredwithout a fixed infrastructure. In the absence of a fixed infrastructure, it poses a challenge in terms ofsecurity. One of the MANET attacks that are often encountered is black hole attacks. A black hole attackis a data retrieval attack by sending fake reply messages to the data sending node that declares itselfas the shortest and fastest node to get to the destination node. Where before reaching the destinationnode, the data packet has been dropped. Black hole attacks have two types of attacks, including; anattack which is only done by one attacker node and a collaborative black hole attack performed bymore than one attacking node. In this study the authors use the model of manhattan mobility gridmovement and routing protocol. One of the routing protocols found in MANET is the DSR routingprotocol. the simulation of this test is done using NS-3 simulator with test scenario based on number ofnodes, number of black hole nodes and the area of simulation area. The test was conducted todetermine the effect of black hole attacks of data transmission with packet delivery ratio testingparameters and total packet loss. From the simulation, the test result shows that black hole attackworks quite significantly with total packet loss 89.6552% and the best packet delivery ratio is 53.3333%